Edukasi Pemanfaatan Madu sebagai Terapi Pendukung untuk Mengatasi Diare pada Anak : Meningkatkan Pengetahuan Ibu melalui Intervensi Edukatif - Suci Sulistyorini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diarrhea remains a major health problem, contributing significantly to morbidity and mortality rates in children, especially in developing countries like Indonesia. This disease is often linked to poor sanitation, lack of access to clean water, and a lack of public understanding of proper hygiene practices. Toddlers are the most vulnerable group to diarrhea because their immune systems are not yet fully developed. Current diarrhea management efforts rely heavily on providing oral rehydration salts (ORS) and, in some cases, the use of antibiotics. However, pharmacological approaches are not always available or appropriate in all situations. Therefore, alternative treatments are needed that are safe, readily available, and scientifically proven to be effective. One natural ingredient with significant potential for treating diarrhea is honey. Honey is known to contain various active substances such as enzymes, antioxidants, and antimicrobial compounds that can fight various pathogens that cause diarrhea. Furthermore, honey is also known to help repair the integrity of the intestinal mucosa, stimulate the growth of beneficial bacteria in the digestive tract, and accelerate the healing process. Although the health benefits of honey are well-known, public knowledge—especially among mothers—about its use as an adjunct therapy for diarrhea remains limited. Recognizing the importance of mothers' role in caring for sick children, especially during diarrhea, educational interventions are needed to improve their understanding. This educational activity aims to equip mothers with accurate, easy-to-understand information that can be applied in their daily lives. In this case, the counseling was conducted at PMB Andina Palembang using communicative media such as leaflets and accompanied by live demonstrations to increase information absorption. To measure the effectiveness of this activity, evaluations were conducted through pretests and posttests using structured questionnaires. The results obtained showed a significant increase in mothers' knowledge scores after participating in the counseling.